The Perils of Voice and the Desire for Stealth Democracy - Theiss-Morse, Elizabeth (Maine Policy Review, 2002)
This article is an address given at the May 2002 Maine Town Meeting sponsored by the Margaret Chase Smith Library in Skowhegan. Elizabeth Theiss-Morse takes issue with each of the alleged beneficial effects of increased participation and deliberation in politics. She presents evidence from her own research with colleague John Hibbing that suggests a more participatory democracy does not necessarily result in better decisions, a better political system or better people. Rather, most Americans would prefer not to have to participate in politics at all. Theiss-Morse explains where this view comes from and, in the end, argues for a civic education process that better prepares young people for the gritty divisiveness of our democratic system.
Keywords: democracy; American politics; voting